Hip-focused strengthening and task-specific movement training for an individual with chronic, recurrent femoroacetabular impingement syndrome. - Atkins, Lee T.; Ede, Kelsey; Reid, Megan; Chan, Daniel (Physical Therapy in Sport, 2025)
Examine the effects of hip-focused strengthening and task-specific movement training for a female who has undergone multiple surgical procedures yet continues to experience chronic, recurrent FAIS-related symptoms. Case Report. A 23-year-old active female with an eleven-year history of FAIS and two previous surgical procedures recently experienced a third recurrence of symptoms brought on by increased physical activity levels. The patient performed progressive exercises focused on improving hip extension, abduction, and external rotation strength. The patient also received task-specific movement training aimed at minimizing hip adduction and internal rotation during movement that provoked her symptoms. Following treatment, the patient's self-reported hip pain during movement improved 2.2 points and was abolished during four of the five activities examined. The patient exhibited strength gains for the hip extensors (22 %), abductors (36 %), and external rotators (20 %). The patient exhibited decreased hip adduction during all activities (mean difference = 10.6°) and decreased hip internal rotation during three of the five activities (mean difference = 3.7°). This case report highlights the effects of hip-focused strengthening and task-specific movement training for a patient with longstanding FAIS and multiple surgical procedures.